A agricultura familiar do norte de Minas no contexto da produção de biodiesel - Maria Ângela Ramos (2011)
This thesis is a study on family agriculture in Northern Minas Gerais. The agricutural background is the National Program of Production and Use of Biodiesel and we adopt the Program’s social guidelines as analytical concepts: the inclusion of family agriculture in the supply chain of biodiesel, security, food sovereignty, labor, and rural poverty reduction. The main objective was to verify whether these guidelines are in fact implemented and the specific objectives relate to the analysis of the reality of these agriculturists: how they produce their crops, work management before and after establishing commercial relations with Petrobras Biocombustível – PBBio, the benefits and difficulties that arise from a new way of organizing their production in accordance with the program’s technical assistance and their prospectives and conditions to remain in this context. A comprehensive field research has been carried out in Northern Minas Gerais towns in three separate stages: Montes Claros, Jaíba, Matias Cardoso, Manga, Rio Pardo de Minas, Taoibeiras e Montezuma. The research timeline ranged from the construction of Montes Claros industrial plant (May and November 2009) to November 2010. The work required a complex methodology using semi-structured interviews, mental maps, non-participant observation, photographs, auditing meetings between agriculturists and related institutions and a workshop with social actors involved in the supply chain (institutions, labor unions, technical assistance, family agriculturists) under technical procedures of group discussions, focus groups, debating and writing reports. Parallel to the field work, a vast literature related to the research was analyzed: 1) The historical conformation of Northern Minas Gerais and its industrialization process; 2) The production of “agrifuels” in general especially on the biodiesel supply chain in Brazil as regulated by PNPB; 3) The social and cultural elements constituent of local family agricultural production involved in the biodiesel chain. Research results point towards considerable changes in the production and labor organization of these agriculturists: since they were involved in the farming of castor beans, their dependence on the biodiesel production chain market grew stronger.